PENYELESAIAN SENGKETA LINGKUNGAN HIDUP MENURUT UNDANG UNDANG N0MOR 32 TAHUN 2009 - TRIWANTO - (Wacana Hukum, 2009)
Abstract: UU No. 32 2009 utilizes various law requirement, either administrative law, civil law, or code penal law. Civil law requirement covers the solution of conflict in environment in court and out of court. The solution of environment in the court covers group accusation, environment organization accusation right, or government accusation right. Through the above it is hoped to give fright effects as well as improve the awareness of the whole stake holders on the importance of environment management for the next generation. Key words: conflict solution, environment